A Striking Result or just a Matter of Misinterpretation? - Katrin Wesche; Susanne Wierum (Kredit und Kapital, 1995)
Die Vereinbarkeit von negativem Geldmengenwachstum mit Hyperinflation In seinem Aufsatz kommt Gersbach (1993) zu dem Ergebnis, daß Hyperinflation mit negativem Geldmengenwachstum vereinbar sei. Im Gegensatz hierzu wird in unserem Kommentar gezeigt, daß nur akzelerierendes Geldmengenwachstum zu ständig steigender Inflation führt. Ausgehend von einer Geldnachfragefunktion vom Cagan-Typ wird die Lösung für rationale Erwartungen hergeleitet und der Zusammenhang zwischen Geldmengenwachstum und Inflation analysiert. – – This comment refers toa paper by Gersbach (1993) on the relationship between money growth and inflation. Contrary to Gersbach's result it is shown that fully anticipated accelerating money growth leads to accelerating inflation. Starting from a money demand function of the Cagan-type, the forward looking rational expectations solution is derived and the relation between money growth and inflation is established.
Keywords: 330